2009
DOI: 10.1002/jmri.22006
|View full text |Cite
|
Sign up to set email alerts
|

Neural specificity of acupuncture stimulation at pericardium 6: Evidence from an FMRI study

Abstract: Purpose: To investigate the neural specificity of pericardium PC6, with the same meridian acupoint PC7 and a treatment-irrelevant acupoint GB37 as separate controls. Materials and Methods:Functional magnetic resonance imaging (MRI) of the whole brain was performed in 36 healthy subjects receiving acupuncture at three acupoints, respectively: the study acupoint (PC6), and control acupoints (PC7 and GB37). A novel nonrepeated eventrelated (NRER) design paradigm was applied to separately detect neural activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 27 publications
1
54
0
4
Order By: Relevance
“…With this study, the sedative effect observed in the clinic during acupuncture for nausea at the PC6 point is also shown in the laboratory (Bai et al, 2010). In our study, the HT7 and Liv3 points were used to increase the sedative effect of acupuncture at PC6.…”
Section: Discussionmentioning
confidence: 75%
“…With this study, the sedative effect observed in the clinic during acupuncture for nausea at the PC6 point is also shown in the laboratory (Bai et al, 2010). In our study, the HT7 and Liv3 points were used to increase the sedative effect of acupuncture at PC6.…”
Section: Discussionmentioning
confidence: 75%
“…[6][7][8]13 Há várias teorias para explicar a analgesia consequente do tratamento com acupuntura. A teoria de Mackenzie preconiza que a estimulação sensorial por agulha provoca reaç ões funcionais aos músculos, vasos e ligamentos inervados pelo mesmo mielótomo.…”
Section: Discussionunclassified
“…Basically, acupuncture stimulation of main acupoints around the body was investigated and evaluated by different molecular imaging modalities. These studies showed that different molecular imaging techniques played important roles in such investigations (Wu et al, 1999b;Litschera and Schikora, 2002;Siedentopf et al, 2002;Lee et al, 2003;Fang et al, 2004;Nakagoshi et al, 2005;Napadow et al, 2005;Yan et al, 2005;Schlunzen et al, 2007;Deng et al, 2008;Lin et al, 2008;Qin et al, 2008;Vas et al, 2008;Zhou and Jin, 2008;Harris et al, 2009;Ho et al, 2009;Kong et al, 2009;Lai et al, 2009;Liu et al, 2009;Sato et al, 2009;Bai et al, 2010;Hsieh et al, 2011).…”
Section: Basic Acupuncture Techniques Assessed With Molecular Imagingmentioning
confidence: 96%